2014
DOI: 10.1016/j.yexmp.2014.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Elevated circulating miR-150 and miR-342-3p in patients with irritable bowel syndrome

Abstract: Background and Aims MicroRNAs (miRNAs) are small non-coding RNAs, which regulate gene expression and are thus of interest as diagnostic markers, and as clues to etiology and targets of intervention. This pilot study examined whether circulating miRNAs are differentially expressed in patients with IBS. Methods miRNA microarrays (Nanostring) were run on the whole blood of 43 participants. Results hsa-miR-150 and hsa-miR-342-3p were found to be significantly elevated (FDR adjusted p ≤ 0.05, ≥1.6 fold change) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
70
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(72 citation statements)
references
References 19 publications
0
70
0
2
Order By: Relevance
“…It has been reported that differential expression of several miRNAs may be correlated with inflammation [29], peripheral circulation [30], immunomodulatory [31], gut microbiota [32], and other processes that are involved in the pathogenesis of IBS-D. For example, Bitar [31] found that miR-155 was expressed in the duodenal epithelium at the acute stage of cholera and could limit the innate immune response of the host, including the inflammation evoked by its own secreted factors. Mansour’s research [32] showed that decreased expression of miR-199b would lead to an increased coliform count.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that differential expression of several miRNAs may be correlated with inflammation [29], peripheral circulation [30], immunomodulatory [31], gut microbiota [32], and other processes that are involved in the pathogenesis of IBS-D. For example, Bitar [31] found that miR-155 was expressed in the duodenal epithelium at the acute stage of cholera and could limit the innate immune response of the host, including the inflammation evoked by its own secreted factors. Mansour’s research [32] showed that decreased expression of miR-199b would lead to an increased coliform count.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there are no generally accepted diagnostic biomarkers for IBS (i.e., the diagnosis is based on clinical symptoms and ruling out other organic disorders, such as GI malignancy, Inflammatory Bowel Diseases, and gastrointestinal (GI) infections). When studying gene expression profiles in common conditions with subclinical histopathology, such as IBS, high sensitivity and accuracy (reproducibility) are needed, as perturbations in gene expression profiles are often subtle [1][2][3] . miRNAs have been identified as both diagnostic and functional targets in IBS 4,5 , and we are particularly interested in assessing their use as circulating biomarkers of IBS-associated biological perturbations 3,4,6,7 .…”
Section: Introductionmentioning
confidence: 99%
“…When studying gene expression profiles in common conditions with subclinical histopathology, such as IBS, high sensitivity and accuracy (reproducibility) are needed, as perturbations in gene expression profiles are often subtle [1][2][3] . miRNAs have been identified as both diagnostic and functional targets in IBS 4,5 , and we are particularly interested in assessing their use as circulating biomarkers of IBS-associated biological perturbations 3,4,6,7 . The clinical utilization of circulating biomarkers is of current interest due to the ease and minimally invasive nature of the collection of the biomarkers' source (e.g., peripheral blood) from patients.…”
Section: Introductionmentioning
confidence: 99%
“…nCounter miRNA panels have been utilized to differentiate between normal and disease states in cancer [70], neurodegeneration [71], and bowel syndrome [72]. Moreover, respective panels have been successfully used for stratification of patients [73][74][75].…”
Section: Emerging Technologiesmentioning
confidence: 99%